Hutan bandar sebagai taman rekreasi di kawasan perumahan - Abu Bakar, Zaleha (2010)
Urban Forest is one of public recreation areas developed by the Local Authority in the administration. The previous location of forest areas located in urban areas but in this day, there is a concept of urban forest that has been developed in the housing areas. Urban Forest is one of the public recreational parks become the focus of society for the purpose of the present exercise and rest, either with family members, friends or individually. Studies carried out are focused on the development of urban forest as a recreational park in residential areas and identify the needs and views of visitor facilities and activities available at this recreation park. The study was conducted to achieve the objectives of the study was the first to identify the concept of urban forest as a recreational park and the second objective, to identify the visitors reaction on the recreational facilities at MPJBT Urban Forest. To achieve the objectives, the authors have been distributing questionnaire forms to visitors in the study. Some 100 sets of forms were distributed to randomly selected visitors. The information obtained was analyzed using the methods Analysis Frequency Statistics and Analysis Scaling Likert for obtains the result by using SPSS software. The findings from this study found the concept of urban forest as a recreation area is different from the existing park in a residential area. In addition, findings from this study found there is still a lack of facilities and activities in this study. Therefore, several recommendations have submitted at the end of this chapter for the management of forest areas to meet all the requirements and needs of the public.